C27 SHOCKWAVE DEFERRED USE IN A CASE OF INFERIOR STEMI. (18th May 2022) - Priolo, L; Ferrarello, S; Buccheri, D; Lombardo, R; Vinci, D
Abstract: A 62–years–old female patient, smoker, hypertension, dyslipidemia and TIA in history, was admitted for inferior STEMI; urgent coronary angiography from radial access was done, revealing diffuse calcific coronary artery disease with thrombotic occlusion of the proximal right coronary artery. Primary PCI was done with a direct implantation of a 3, 0/24 mm drug–eluting stent. The stent expansion was not optimal in the mid–portion, due to severe calcification, requiring then post–dilatations. Nevertheless, the use of several non–compliant balloons (3, 0/12 mm, 3, 0/8 mm, 3, 0/6 mm, 3, 25/12 mm) was not effective to fully expand the stent, even dilating at very high pressure (rupturing one of the balloon). A ventricular fibrillation episode complicated the procedure, promptly resolved. After the stenting, even if not fully expanded, TIMI 3 flow was gained, with ST segment elevation resolution, in a quite asymptomatic patient; no more devices were available, so the procedure was stopped and the patient transferred in the coronary care unite. A second procedure was scheduled with the support of the intravascular lithotripsy device (Shockwave). Through the radial access the second PCI was done, using at first the Shockwave balloon 2, 5/12 mm, with its total 8 treatments; then the Shockwave balloon 3, 0/12 mm was used, effective at the seventh treatment in the final rupture of the calcific lesion, obtaining the full expansion of the stent. A good final angiographic result was documented, the patient tolerated very well the procedure.